2017
DOI: 10.1371/journal.pone.0173762
|View full text |Cite|
|
Sign up to set email alerts
|

The association between methylphenidate treatment and the risk for fracture among young ADHD patients: A nationwide population-based study in Taiwan

Abstract: Attention-deficit hyperactivity disorder (ADHD) is associated with higher risk for fracture. Whether the medical treatment for ADHD would mitigate the risk remains unclear. In this study, we sought to investigate the effect of methylphenidate treatment on risk for fracture, as well the moderational role of treatment duration on the risk of fracture, in a large national sample. Cases less than 18 years old were identified from Taiwan’s National Health Insurance Research Database with a new primary diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 58 publications
2
48
0
Order By: Relevance
“…Titles and abstracts were screened and full texts were retrieved for further assessment of 26 relevant records, of which 10 studies were found to be relevant. Six of the studies [6,[13][14][15][16][17] were conducted using nationwide databases, with two [15,16] from the same nationwide claim database in Taiwan, three others [4,18,19] from insurance claim databases and one [5] from GP database, all with substantial numbers of patients. All studies evaluated physical injuries as the outcome, which was defined as medically attended injuries at any point of care, identified diagnoses for injury on database records, or through entries for trauma or transport-related injuries on medical records.…”
Section: Resultsmentioning
confidence: 99%
“…Titles and abstracts were screened and full texts were retrieved for further assessment of 26 relevant records, of which 10 studies were found to be relevant. Six of the studies [6,[13][14][15][16][17] were conducted using nationwide databases, with two [15,16] from the same nationwide claim database in Taiwan, three others [4,18,19] from insurance claim databases and one [5] from GP database, all with substantial numbers of patients. All studies evaluated physical injuries as the outcome, which was defined as medically attended injuries at any point of care, identified diagnoses for injury on database records, or through entries for trauma or transport-related injuries on medical records.…”
Section: Resultsmentioning
confidence: 99%
“…7 Another retrospective cohort study of more than 6,000 cases from Taiwan, reported an adjusted hazard ratio of 0.77 (95%CI, 0.63-0.94) among cases with ADHD treated with MP, compared to cases with ADHD who were not treated with MP. 6 The main important finding of this study is the establishment of a dose-response relationship between MP use and fracture incidence, which is one of the basic criteria for determining causation. 23 In addition, the present study shows that treatment of ADHD reduces the odds for fractures, despite its reportedly adverse effects on bone mineral density.…”
Section: Discussionmentioning
confidence: 99%
“…This stratification was based on the study by Chen et al, who found lower fracture incidence among subjects who used MP for more than 180 days, compared to subjects with ADHD who did not use it at all. 6 Fracture incidence in these five groups was presented as the percentage of subjects with fractures within each group. In addition, the unadjusted odds ratio (OR) of fractures was calculated for each group using logistic regression.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations